2017
DOI: 10.21815/jde.017.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Community‐Based Education in U.S. Dental Schools

Abstract: This review of U.S. dental schools' clinical curricula suggests that the basic structure of clinical education has not changed significantly in the past 60 years, although important developments include the introduction of competency-based education and community-based clinical education. Most dental schools still have a two-year preclinical curriculum and a two-year clinical curriculum, and most schools still operate a large clinical facility where students receive the bulk of their clinical education and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
15
0
5
Order By: Relevance
“…Dental school clinics that operate as teaching laboratories do not provide an adequate setting to model practice in the 21 st century. Licari and Evans point to the difficulties schools have in making changes in clinical education, given current crowded curricula and the focus on restorative services 11 . They report that the teaching of the restoration of a single tooth and missing teeth occupies 66% of clinical clock hours and 45% of total curricular time.…”
Section: Areas Of Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Dental school clinics that operate as teaching laboratories do not provide an adequate setting to model practice in the 21 st century. Licari and Evans point to the difficulties schools have in making changes in clinical education, given current crowded curricula and the focus on restorative services 11 . They report that the teaching of the restoration of a single tooth and missing teeth occupies 66% of clinical clock hours and 45% of total curricular time.…”
Section: Areas Of Challengementioning
confidence: 99%
“…Licari and Evans observe that the fundamental organization of dental school clinics is not conducive to managing complex patients because predoctoral students provide nearly 100% of treatment 11 . Faculty members act as supervisors or “checkers” of the care provided by students.…”
Section: Areas Of Challengementioning
confidence: 99%
“…Another benefit of community‐based dental programs is the exposure of dental students to racially and ethnically diverse populations with definite dental needs and the limited access to oral healthcare. As recommended by the Dental Pipeline Project, The OSU CoD revised the curriculum with additional courses to prepare dental students to embrace the culture of the dental patients encountered in the community‐based facilities . The revised curriculum embraced the themes of community service, academics, and citizenship .…”
Section: Discussionmentioning
confidence: 99%
“…59 However, one study found that students' attitudes towards treating underserved populations became less positive as they progressed through the four-year curriculum. Most U.S. dental schools provide a community-based learning component for dental students in their third and fourth years.…”
Section: Recommendations For Incorporation Of Frameworkmentioning
confidence: 99%
“…Most U.S. dental schools provide a community-based learning component for dental students in their third and fourth years. 59 However, one study found that students' attitudes towards treating underserved populations became less positive as they progressed through the four-year curriculum. 60 These negative attitudes can deter future dentists from ofering treatment to members of underserved communities, such as patients from ethnic minority groups and senior patients.…”
Section: Recommendations For Incorporation Of Frameworkmentioning
confidence: 99%